PEMANFAATAN KRIM SANTAN SEBAGAI MINYAK ALTERNATIF GUNA MENURUNKAN ANGKA KEJADIAN ANEMIA PADA REMAJA - Lina (PPPM POLTESA, 2022)
Cream of coconut milk is a thicker viscous substance produced from coconut milk which can be utilized as oil from coconut cream. Processing of coconut cream into oil is a processed oil product that has a clear color and has a distinctive coconut odor and has a long shelf life. The purpose of this study was to determine the organoleptic test (taste, color, texture, and aroma) of coconut cream oil according to SNI. This study used an experimental design study method, which consisted of 3 treatments used, namely the addition of Fe tablets with a ratio of F1 (1 Fe capsule : 1 Vitamin A capsule), F2 (1 ½ Fe capsule : 1 ½ vitamin A), F3 (2 Fe capsule: 2 vitamin A), then the Fe content was analyzed. The data obtained using ANOVA (Analysis Of Variance) was then identified by organoleptic tests and the content of iron (Fe) was tabulated in tabular form. The results of the organoleptic test on coconut cream oil were more dominant in the F3 treatment (2 Fe capsules: 2 vitamin A), and less favored in the F1 treatment. The results of testing the content of iron (Fe) in treatment 1 was 0.0107 and in treatment 2 was 0.0543 while in treatment 3 it was 0.0133. The results of the data showed that there was an increase in iron (Fe) content in treatment 2 of 0.0543. The use of heat in the process of cooking food greatly affects the nutritional value of food. The frying process is food processing using high temperatures above 160⁰C which can reduce the fat content and destroy vitamins and minerals, one of which is iron.